Phenotypic instability and epigenetic variability in a diploid potato of hybrid origin, Solanum ruiz-lealii - Marfil, Carlos Federico (2009)
Background: The wild potato Solanum ruiz-lealii Brüch. (2n = 2x = 24), a species of hybrid origin, is endemic to Mendoza province, Argentina. Recurrent flower malformations, which varied among inflorescences of the same plant, were observed in a natural population. These abnormalities could be the result of genomic instabilities, nucleus-cytoplasmic incompatibility or epigenetic changes. To shed some light on their origin, nuclear and mitochondrial DNA of plants with normal and plants with both normal and malformed flowers (from here on designated as plants with normal and plants with abnormal flower phenotypes, respectively) were analyzed by AFLP and restriction analyses, respectively. Also, the wide genome methylation status and the level of methylation of a repetitive sequence were studied by MSAP and Southern blots analyses, respectively. Results: AFLP markers and restriction patterns of mitochondrial DNA did not allow the differentiation of normal from abnormal flower phenotypes. However, methylation patterns of nuclear DNA discriminated normal and abnormal flower phenotypes into two different groups, indicating that abnormal phenotypes have a similar methylation status which, in turn, was different from the methylation patterns of normal phenotypes. The abnormal flower phenotype was obtained by treating a normal plant with 5-Azacytidine, a demethylating agent, giving support to the idea of the role of DNA methylation in the origin of flower abnormalities. In addition, the variability detected for DNA methylation was greater than the detected for nucleotide sequence. Conclusion: The epigenetic nature of the observed flower abnormalities is consistent with the results and indicates that in the diploid hybrid studied, natural variation in methylation profiles of anonymous DNA sequences could be of biological significance.